Evaluating the link between the dietary intake of vitamin B and constipation: a population-based study - Yang, Wenyuan; Jiang, Chenyu; Shao, Yaojian; Gu, Shicheng; Hong, Mingqi (Frontiers in Nutrition, 2025)
BackgroundPrior research has established a correlation between dietary micronutrient intake and the risk of developing constipation. However, the potential link between vitamin B intake and constipation has yet to be fully explored. This study sought to assess the association between chronic constipation and dietary vitamin B intake based on National Health and Nutrition Examination Survey (NHANES) data.MethodsThis study employed NHANES data collected between 2005 and 2010, including a total of 13,885 participants 20 + years of age. Dietary intake of vitamins B1, B2, niacin, B6, folic acid, choline, and B12 was assessed using the first 24-h dietary recall interview. Constipation was defined based on the Bristol Stool Form Scale (BSFS). A weighted logistic regression model and restricted cubic spline (RCS) analysis were utilized to adjust for demographic and lifestyle-related variables and probe the relationship between B vitamin intake and constipation. Statistical significance was set at a two-tailed p-value < 0.05. Confidence intervals (95% CIs) were calculated using weighted logistic regression.ResultsThe analysis revealed a nonlinear inverse correlation between dietary intake of all examined B vitamins and constipation risk. In particular, a significant reduction in constipation odds was observed in the highest intake quartiles of niacin (OR = 0.76, 95% CI: 0.59–0.99, p for trend = 0.003), folate (OR = 0.61, 95% CI: 0.48–0.79, p for trend < 0.001), and choline (OR = 0.77, 95% CI: 0.60–1.00, p for trend = 0.05) when using a model that was fully adjusted. Subgroup analyses further indicated that alcohol consumption significantly modified the relationship between folate (p for interaction = 0.003), vitamin B1 (p for interaction = 0.004), niacin (p for interaction = 0.04), choline (p for interaction = 0.02), and constipation.ConclusionIncreased dietary intake of B vitamins may contribute to a reduced risk of constipation, particularly among specific population subgroups. These results offer additional support for the potential role of dietary modifications in promoting gut health.